Human Security Policy Initiative on Catastrophic Disaster and Crisis Response in Indonesia - Liu, Fu-Kuo; Fitrah, Elpeni (KnE Social Sciences, 2023)
This paper discusses the internalization of global ideas in a country’s national policies. This paper reviews the application of the human security concept to Indonesia’s domestic policies, especially on the issue of catastrophic disaster and crisis response. This topic arises as Indonesia has historically experienced various crises, such as the 1997 financial crisis, the health crisis due to the 2002 SARS pandemic outbreak, and the humanitarian crisis caused by the 2004 tsunami disaster. In addition, Indonesia is threatened by other issues, such as domestic conflict, separatism, terrorism, and environmental problems. All of these issues, according to experts, have an equivalent impact on conflict and significantly affect the security of citizens. Therefore, this article intends to discover the capacity and ability of Indonesia to apply human security ideas in its domestic policies. This paper uses two approaches to achieve its objective: the human security approach according to the global perspective and the policy network approach in public policy studies. This paper argues that the idea of human security has not yet become a platform in the formulation of security policy in Indonesia. However, the basic principles of the concept of human security are contained in the national constitution. Besides, in the disaster and crisis management context directly related to human security, the state is still working alone. It has not optimized all the resources and non-governmental actors to work together to produce the community’s specific policies. Keywords: Human Security, Policy Network, Crisis, Disaster, Indonesia